2018
DOI: 10.1039/c8cp02119h
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure-assisted X-ray-induced damage as a new route for chemical and structural synthesis

Abstract: X-ray induced damage has been known for decades and has largely been viewed as a tremendous nuisance. We, on the other hand, harness the highly ionizing and penetrating properties of hard X-rays to initiate novel decomposition and synthetic chemistry. Here, we show that powdered cesium oxalate monohydrate pressurized to ≤0.5 GPa and irradiated with X-rays of energies near the cesium K-edge undergoes molecular and structural transformations with one of the final products exhibiting a new type of bcc crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…4,5 X-ray-induced effects are somewhat less well studied in conventional inorganic systems, despite being implicated in a number of interesting phenomena. Examples include decomposition, [6][7][8] conductivity enhancement, [9][10][11][12][13] colour changes, 14 spincrossover, 15 charge transfer, 16,17 cell-parameter changes, 18 crystallisation, 19 and amorphisation. 20,21 X-ray irradiation has been found to induce changes in the resistivity of magnetoresistive manganites (A 3+ 1−x B 2+…”
Section: Introductionmentioning
confidence: 99%
“…4,5 X-ray-induced effects are somewhat less well studied in conventional inorganic systems, despite being implicated in a number of interesting phenomena. Examples include decomposition, [6][7][8] conductivity enhancement, [9][10][11][12][13] colour changes, 14 spincrossover, 15 charge transfer, 16,17 cell-parameter changes, 18 crystallisation, 19 and amorphisation. 20,21 X-ray irradiation has been found to induce changes in the resistivity of magnetoresistive manganites (A 3+ 1−x B 2+…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this work triggered, detailed investigations of high-pressure assisted X-ray induced damage. 422 In addition, the authors concluded that such processes can be a new route for he synthesis of novel materials and structures.…”
Section: Systems and Applicationsmentioning
confidence: 99%
“…Heya et al (Heya et al, 2020, Heya et al, 2021) irradiated pentacene to obtain nanographene. Evlyukhin et al (Evlyukhin et al, 2018) reported the combination of high-pressure and X-ray exposure for the synthesis of oxalates. Miszta et al (Miszta et al, 2014) performed XRL on colloidal inorganic nanocrystals, causing the cross-linking of the ligand molecules coating the crystals, inducing a selective protection to cation exchange.…”
Section: Othersmentioning
confidence: 99%